Immunization With a DNA Vaccine Encoding the Toxoplasma gondii’ s GRA39 Prolongs Survival and Reduce Brain Cyst Formation in a Murine Model - Zhu, Yuchao; Xu, Yanan; Hong, Lu; Zhou, Chunxue; Chen, Jia (Frontiers in Microbiology, 2021)
Toxoplasma gondii, an obligate intracellular protozoan parasite, can cause severe disease in almost all warm-blooded animals and humans. To evaluate the immunogenicity and protective efficacy of T. gondii GRA39 (TgGRA39) in mice by using DNA immunization, we constructed a recombinant eukaryotic plasmid pVAX-TgGRA39. The specific immune responses in immunized mice were analyzed by serum antibody and cytokine measurements, lymphocyte proliferation assays and flow cytometry of T lymphocyte subclasses. Also, protective efficacy against acute and chronic T. gondii infection was assessed by observing the survival time after challenge with the highly virulent RH strain of T. gondii (Genotype I) and counting the number of cyst-forming in brain at 4 weeks post-infection with the cyst-forming PRU strain of T. gondii (Genotype II), respectively. Our results showed that DNA immunization with pVAX-GRA39 via intramuscular injection three times, at 2-week intervals could induce a strong humoral and cellular immune response, indicated by higher levels of IgG and IgG2a antibodies (a slightly elevated IgG2a to IgG1 ratio), and higher levels of cytokines IFN-γ, IL-2, IL-12, IL-17A, IL-17F, IL-22 and IL-23 and percentages of CD3 + CD4 + CD8 - and CD3 + CD8 + CD4 - T cells, in contrast to non-immunized mice. A significant increase in the expression level of IL-6, TGF-β1, IL-1β and the transcription factor factors RORγt, RORα and STAT3 involved in the activation and pathway of Th17 and Tc17 cells, was also observed. However, no significant difference was detected in level of IL-4 and IL-10 (p > 0.05). These effective immune responses had mounted protective immunity against T. gondii infection, with a prolonged survival time (16.80±3.50 days) and reduced cyst numbers (44.5%) in comparison to the control mice. Our data indicated that pVAX-TgGRA39 could induce effective humoral and Th1-type, Th17 and Tc17 cellular immune responses, and may represent a promising vaccine candidate against both acute and chronic T. gondii infection.